Elite and sub-elite athletes and pregnancy: training, performance, health and psychological aspects across the pre-, peri-, and postnatal stages: A scoping review - Nolte, J.; Thal, I.; Büthe, E.; Weber, S.; Platen, P.; Legerlotz, K. (Sports Medicine - Open, 2026)
Background The number of elite female athletes navigating pregnancy continues to rise, yet the intersection of high-performance sport and motherhood remains understudied. This scoping review summarizes the literature on training, performance, physical health, and psychological aspects before, during, and after pregnancy in elite and sub-elite athletes (tiers 3-5). The aim is to identify knowledge gaps and to inform future research.